EFFICIENCY AND SAFETY OF NEURAMINIDASE INHIBITOR OSELTAMIVIR FOR CHILDREN - A.S. Darmanyan (Педиатрическая фармакология)
Every year 3 to 5 million people suffer from flu. Children are most susceptible to flu. At the moment, the main methods of flu prophylaxis and treatment are flu vaccination and antivirus medications. Of the tested anti virus medications, 3 groups are most interesting and interferon inductors, м 2=channel blockers (derivative of adamantine) and neuraminidase inhibitors. neuraminidase inhibitors are a brand new type of virus infection therapy — they selectively inhibit activity of flu virus neuraminidases, which restrains virus from getting into the cell, exit of virion from the cell before the reproduction cycle is over and new cells are affected. Oseltamivir — one of the new neuraminidase inhibitors — can be used for a safe and efficient flu treatment and prophylaxis among adults; yet recently this medication has been authorized for children over 1 year of age, basing upon the findings of randomized controlled surveys. Data shows that usage of oseltamivir reduces the period of diseases and severity of acute flu symptoms for children with no side diseases, as well as for children suffering from cardiovascular and bronchopulmonary system diseases; besides this medication reduces the risk of secondary flu complications.Key words: neuraminidase inhibitors, oseltamivir, flu, bird flu, antivirus medications.